Do Exchange Rates Affect Inflation? Evidence from Emerging Market Economies - Baki Demirel; Barış Alpaslan; Emre Güneşer Bozdağ (Koç University-TÜSİAD Economic Research Forum (ERF), 2013)
After 1980s, chronic inflation in Turkey has shaken the confidence in the domestic currency, and thus operating debit-credit transactions through dollars. The aim of this study is to analyse the impact of exchange rate pass-through into inflation in both Turkey and emerging market economies that were highly dollarized and shifted to a flexible exchange rate regime, together with inflation targeting policy in an attempt to switch to the advanced economy, and to examine whether stabilization programs under flexible exchange rate regimes and particularly inflation targeting policy may eliminate dollarization in the periods 1995-2001 and 2002-2010.
Keywords: E42; E52; E58; 330; De-Dollarization; Inflation Targeting; Exhange Rate Pass-Through